Can I Ask That?: Helping Well-Meaning Mediators Prevent Common Capacity Assessment Pitfalls - Dan Berstein; Kristen Blankley (Washington University Journal of Law and Policy, 2026)
One of the initial conundrums presented to mediators upon intake is evaluating a party’s capacity to participate in the mediation. Are the parties fearful of each other? Is there an improper power dynamic present? Might they be impeded from being able to make a decision? Mediators have a duty to ensure parties have the capacity to participate. This means ensuring they can understand what is going on, use reason to explore a decision, appreciate how it impacts them, and freely express a choice. How does a mediator go about evaluating a party’s capacity appropriately? It may seem tempting to ask questions about a party’s potential disability, but the Americans with Disabilities Act (ADA) protects both people with disabilities and those who are “regarded as” having disabling health conditions from experiencing discriminatory treatment—including protection from inappropriate inquiries about possible disabilities. Although the industry standard is varied across subject-matter, sometimes there are policies and practices that inappropriately link capacity assessments to disabilities. This Article evaluates the ethical and legal considerations surrounding capacity determinations. Through a foundational understanding of clinical and legal definitions of ‘capacity,’ this Article considers the various forms of capacity assessments and the mistakes that often befall these processes. The Article will provide practical tools and recommendations to stay within ethical boundaries when assessing the capacity of parties in any mediation.
Keywords: #MediationEthics; #ADAinMediation; #MediatorTools; #MediationPractice